2016
DOI: 10.1002/wdev.235
|View full text |Cite
|
Sign up to set email alerts
|

Maternal AP determinants in the Drosophila oocyte and embryo

Abstract: An animal embryo cannot initiate its journey of forming a new life on its own. It must rely on maternally provided resources and inputs to kick-start its developmental process. In Drosophila, the initial polarities of the embryo along both the anterior-posterior (AP) and dorsal-ventral (DV) axes are also specified by maternal determinants. Over the past several decades, genetic and molecular studies have identified and characterized such determinants, as well as the zygotic genetic regulatory networks that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 179 publications
(561 reference statements)
0
12
0
Order By: Relevance
“…We and others have previously shown that chromatin organisation in Drosophila is established at nc14, coincident with ZGA (Hug et al, 2017;Ogiyama et al, 2018). While a small number of genes are zygotically expressed prior to the major wave of ZGA (Lott et al, 2011), maternally provided cues are responsible for establishing the major anterior-posterior and dorsoventral axes (Ma et al, 2016;Stein and Stevens, 2014). Therefore, by ZGA, cells in different regions of the embryo contain different developmental transcription factors, have different patterns of chromatin accessibility (Cusanovich et al, 2018), and are primed to express different genes.…”
Section: Whilementioning
confidence: 87%
“…We and others have previously shown that chromatin organisation in Drosophila is established at nc14, coincident with ZGA (Hug et al, 2017;Ogiyama et al, 2018). While a small number of genes are zygotically expressed prior to the major wave of ZGA (Lott et al, 2011), maternally provided cues are responsible for establishing the major anterior-posterior and dorsoventral axes (Ma et al, 2016;Stein and Stevens, 2014). Therefore, by ZGA, cells in different regions of the embryo contain different developmental transcription factors, have different patterns of chromatin accessibility (Cusanovich et al, 2018), and are primed to express different genes.…”
Section: Whilementioning
confidence: 87%
“…21,32,33 The quick shutdown of hb transcription (<3 min into the nc14 interphase as estimated in our model; Table 1) provides a mechanism for hb P2 promoter to respond to the Bcd gradient as its primary input in forming an expression boundary in a Bcd concentration-dependent manner. 3 This relatively reliable input-output relationship between Bcd and hb transcription has been suggested to be important for AP pattern formation in a manner that is robust to embryo size variations. 3,[34][35][36][37][38] The estimated parameters in our current study are consistent with existing estimates and yield new insights into transcription regulatory mechanism during embryonic development.…”
Section: -31mentioning
confidence: 98%
“…3 This relatively reliable input-output relationship between Bcd and hb transcription has been suggested to be important for AP pattern formation in a manner that is robust to embryo size variations. 3,[34][35][36][37][38] The estimated parameters in our current study are consistent with existing estimates and yield new insights into transcription regulatory mechanism during embryonic development. For example, our estimated k on (prior to shutdown) and k off are both fast, as those at earlier nuclear cycles reported by Xu et al, 15 despite the significant differences in our experimental and modeling approaches.…”
Section: -31mentioning
confidence: 98%
See 2 more Smart Citations